Proceedings of the 6th International Conference on Educational Research and Innovation (ICERI 2018) 2019
DOI: 10.2991/iceri-18.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Enganging Balinese Culture and Technology in Digital Era: A Review to Foster Primary Teachers’ Competencies

Abstract: Qualified elementary teachers are teachers who have competencies that meet the demands of the 21st century and the industry revolution 4.0. The 21st century competencies are ICT competency, cultural competency, the competency to implement culture-based learning, and personal competence in the form of self-efficacy. One way for developing such competencies in the digital age is by developing a learning resource which integrates Balinese culture with technology. This learning resource helps the elementary teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The increase is to be able to ensure the economic sustainability of the community. In this digital era, innovation with the support of technology can be integrated with Balinese culture [13]. Banjar can manage citizen data with more valuable such as the purchasing power of each citizen.…”
Section: Innovation By Developing the Concept Of "Smartmentioning
confidence: 99%
“…The increase is to be able to ensure the economic sustainability of the community. In this digital era, innovation with the support of technology can be integrated with Balinese culture [13]. Banjar can manage citizen data with more valuable such as the purchasing power of each citizen.…”
Section: Innovation By Developing the Concept Of "Smartmentioning
confidence: 99%
“…This foundation has a significant contribution to sustainable human resources development in the 21 st century. The foundation can be constructed through the role of elementary school teachers who play the role as the spearhead for the human resources development at that level (Riastini, Widowati, et al, 2019;Sumaryanta et al, 2018). In other words, elementary school teachers are a vital aspect of the educational development.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there was no integration between the knowledge and skills that the students have acquired. A study with 213 elementary school teachers in Bali showed that there is a cultural discontinuity in teaching, and many teachers cannot use technology to support teaching (Riastini, Widowati, et al, 2019). It affects meaningful learning and students' outcome.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Balinese folklore, which is well known as Satua Bali, can be integrated into science contents. One of them is I Buta Teken I Lumpuh (A Blind Man and A Paralyzed Man) that can be related to the five senses (eyesight) and human skeleton as well as diseases related to them [12,13]. Therefore, ethno-pedagogy can help students to understand and find the relevance of science to themselves [14], while developing their cultural literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Another likely reason is that teachers still do not know much and do not have enough skill about how to relate the local culture (local genius) and mobile technology to learning contents in one time. Thus, teachers have never related Balinese folklore to elementary school science contents, due to the lack of understanding and the skill [13]. The condition is worsened by the fact that the students are not familiar with Balinese folklore, so that the teachers do not see any potentiality of Balinese folklore for science education.…”
Section: Introductionmentioning
confidence: 99%